2011
DOI: 10.1021/pr2003352
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profiling of Lung Granuloma in Mycobacterium tuberculosis Infected Guinea Pigs: Ex vivo 1H Magic Angle Spinning NMR Studies

Abstract: A crucial and distinctive feature of tuberculosis infection is that Mycobacterium tuberculosis (Mtb) resides in granulomatous lesion at various stages of disease development and necrosis, an aspect that is little understood. We used a novel approach, applying high resolution magic angle spinning nuclear magnetic resonance spectroscopy (HRMAS NMR) directly to infected tissues, allowing us to study the development of tuberculosis granulomas in guinea pigs in an untargeted manner. Significant up-regulation of lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
136
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(158 citation statements)
references
References 51 publications
20
136
2
Order By: Relevance
“…This protein was shown to partially depend on the ESX-5 secretion system for export. It would be interesting to see if secreted ALD has a complementary role to play, particularly because the relative quantities of certain amino acids, such as alanine, are found to increase in granulomatous lesions (63,64). Altogether, our findings point toward an important function of the three replicate ESAT-6 regions of ESX-5 in protein secretion and virulence of mycobacteria.…”
Section: Discussionmentioning
confidence: 77%
“…This protein was shown to partially depend on the ESX-5 secretion system for export. It would be interesting to see if secreted ALD has a complementary role to play, particularly because the relative quantities of certain amino acids, such as alanine, are found to increase in granulomatous lesions (63,64). Altogether, our findings point toward an important function of the three replicate ESAT-6 regions of ESX-5 in protein secretion and virulence of mycobacteria.…”
Section: Discussionmentioning
confidence: 77%
“…Inside the phagosome of the macrophage or inside granulomas, the access to high glucose concentrations is restricted. Data about the metabolic composition of the M. tuberculosis-containing vacuoles inside macrophages are lacking, but mass spectrometry analysis determining the metabolic pool in the granulomas of guinea pigs have been performed (16). The detected levels of glucose or intermediates of the glycolysis were rather low, while free amino acids, organic acids, and lipid components accumulated during infection.…”
Section: Discussionmentioning
confidence: 99%
“…When pyruvate was offered as a carbon substrate to growing M. tuberculosis cells, high levels of acetate were detected in the supernatant of the culture. As the pyruvate concentration in macrophages and inside granulomas is considered rather low (15,16) and is most likely not a physiological carbon source for M. tuberculosis, we analyzed whether growth on fatty acids would also result in acetate secretion. In principle, acetyl-CoA and to a lesser extent propionylCoA are generated in the course of ␤-oxidation of fatty acids, turning fatty acids into a potential source for acetate formation.…”
Section: Growth On Fatty Acids Induces Acetate Formation In M Tubercmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, studies using scanning electron and atomic force microscopy revealed that the M.tb cell wall from MDRand XDR-strains differs from susceptible strains (Velayati et al, 2009a(Velayati et al, , 2009b(Velayati et al, , 2010. Experiments analyzing infected granulomas by using high-resolution magic angle spinning nuclear magnetic resonance (HR-MAS-NMR) showed that we are capable of analyzing the cell wall of M.tb w h e n i n s i d e o f t h e g r a n u l o m a w i t h o u t f u r t h e r manipulation (Somashekar et al, 2011). The introduction of novel reporters that can be used for selective labeling of the cell wall of M.tb during infection in vitro and in vivo is already allowing us to see how the cell wall of M.tb is remodeling during infection .…”
Section: Discussionmentioning
confidence: 97%